Computing Wiener and Hyper-Wiener Indices of Zero-Divisor Graph of ℤℊ3×ℤI1I2. (19th September 2022) - Liu, Yonghong; Rauf, Abdul; AdnanAslam,; Ishaq, Saira; Issa, Abudulai
Abstract : Let S = ℤ ℊ 3 × ℤ I 1 I 2 be a commutative ring where ℊ, I 1 and I 2 are positive prime integers with I 1 ≠ I 2 . The zero-divisor graph assigned to S is an undirected graph, denoted as Y S with vertex set V(Y (S)) consisting of all Zero-divisor of the ring S and for any c, d ∈ V(Y (S)), c d ∈ E Y S if and only if cd =0. A topological index/descriptor is described as a topological-invariant quantity that transforms a molecular graph into a mathematical real number. In this paper, we have computed distance-based polynomials of Y R i-e Hosoya polynomial, Harary polynomial, and the topological indices related to these polynomials namely Wiener index, and Hyper-Wiener index.